Fabrication of a Cu(InGa)Se2 Thin Film Photovoltaic Absorber by Rapid Thermal Annealing of CuGa/In Precursors Coated with a Se Layer - Chun-Yao Hsu; Peng-Cheng Huang; Yu-Yao Chen; Dong-Cherng Wen (International Journal of Photoenergy)
Cu(InGa)Se2 (CIGS) thin film absorbers are prepared using sputtering and selenization processes. The CuGa/In precursors are selenized during rapid thermal annealing (RTA), by the deposition of a Se layer on them. This work investigates the effect of the Cu content in precursors on the structural and electrical properties of the absorber. Using X-ray diffraction, field emission scanning electron microscopy, Raman spectroscopy, and Hall effect measurement, it is found that the CIGS thin films produced exhibit facetted grains and a single chalcopyrite phase with a preferred orientation along the (1 1 2) plane. A Cu-poor precursor with a Cu/() ratio of 0.75 demonstrates a higher resistance, due to an increase in the grain boundary scattering and a reduced carrier lifetime. A Cu-rich precursor with a Cu/() ratio of 1.15 exhibits an inappropriate second phase () in the absorber. However, the precursor with a Cu/() ratio of 0.95 exhibits larger grains and lower resistance, which is suitable for its application to solar cells. The deposition of this precursor on Mo-coated soda lime glass substrate and further RTA causes the formation of a MoSe2 layer at the interface of the Mo and CIGS.